2011
DOI: 10.1186/1475-2875-10-173
|View full text |Cite
|
Sign up to set email alerts
|

Urban malaria and associated risk factors in Jimma town, south-west Ethiopia

Abstract: BackgroundMalaria kills millions around the world. Until recently it was believed to be a disease of rural areas, since the Anopheles mosquito, which transmits Plasmodium species breeds in rural areas. Urban malaria is emerging as a potential, but "avertable" crisis, in Africa. In view of the rapidly growing number of small and medium-sized towns in Ethiopia there is a pressing need to improve the understanding of the epidemiology of malaria. Therefore, the aim of this study was to determine malaria prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
117
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(163 citation statements)
references
References 29 publications
22
117
9
Order By: Relevance
“…(17) The use of insecticide-treated nets proved to be able to protect humans from the bite of mosquitoes / malaria vectors. (18,19) Not using wire netting will increase the risk of suffering from malaria 10.55 times and these results are consistent with the research of Kuswanto, (20) who conducted research on malaria risk factors in Banyumas in 2005. Those not using insect repellent are at 6.46-fold increased risk to suffer from malaria.…”
Section: Discussionsupporting
confidence: 80%
“…(17) The use of insecticide-treated nets proved to be able to protect humans from the bite of mosquitoes / malaria vectors. (18,19) Not using wire netting will increase the risk of suffering from malaria 10.55 times and these results are consistent with the research of Kuswanto, (20) who conducted research on malaria risk factors in Banyumas in 2005. Those not using insect repellent are at 6.46-fold increased risk to suffer from malaria.…”
Section: Discussionsupporting
confidence: 80%
“…This holds true in other P. vivax and P. falciparum co-endemic countries such as Ethiopia and Solomon Islands where the relative proportion of P. vivax cases has drastically increased. [90][91][92][93] The data also indicate a change in the proportion of Pfmsp2 alleles over time. The current study demonstrated that 80% of P. falciparum isolates had 3D7-type alleles.…”
Section: Discussionmentioning
confidence: 76%
“…Plasmodium, the causative agent of malaria kills millions of people every year (Alemu et al, 2011). Most of the Apicomplexa have been shown to contain a secondary four membrane-bound nonphotosynthetic plastid (apicoplast) that is essential for the parasite survival (reviewed in Oborník et al, 2009 or Kalanon andMcFadden, 2010).…”
Section: Introductionmentioning
confidence: 99%